Contrast-Enhanced Mammography in the Diagnosis of Breast Angiosarcoma. (13th August 2021) - Kacen, Maya Grisaru; Sangle, Nikhil; Kornecki, Anat
Abstract : A 60-year-old female presented for further assessment of a new right breast lump (November 2020). She had a history of a stage I (T1bN0M0) right breast invasive mammary carcinoma, grade 2 (score 7/9) with receptors ER/PR-negative, HER2/neu-positive, diagnosed four years prior to her current presentation. At that time, she was treated with a right breast lumpectomy and local radiation. Breast assessment with contrast-enhanced mammography showed new skin thickening with associated enhancement within the palpable region. Histology of subsequent ultrasound-guided biopsy found radiation-induced breast angiosarcoma. Breast angiosarcoma is a rare entity that represents less than 1% of all breast cancers. To our knowledge, this is the first case describing the imaging findings of breast angiosarcoma on contrast-enhanced mammography.